Charting the routes to commercialization: The absorption and transfer of energy conservation technologies. (4th August 2014) - Kingsley, Gordon; Bozeman, Barry
This study examines how innovations in Energy Conservation Technologies (ECT's) developed through public sponsorship become commercialized. In the typical ECT project, public support is used as a catalyst bringing public and private organizations together to perform the work. The variety of routes to commercialization this creates can be analysed using two concepts: absorption and transfer. Absorption is adoption of an ECT by an organization participating in the project. Transfer is adoption by non–participants. Two cases sponsored by the New York State Energy Research and Development Authority (the Energy Authority) are analysed. In the first case commercialization is limited to the absorption process. In the second case both absorption and transfer are used in commercialization.